If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11 + -2(8 + 3p) = 7 * 7 11 + (8 * -2 + 3p * -2) = 7 * 7 11 + (-16 + -6p) = 7 * 7 Combine like terms: 11 + -16 = -5 -5 + -6p = 7 * 7 Multiply 7 * 7 -5 + -6p = 49 Solving -5 + -6p = 49 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + -6p = 49 + 5 Combine like terms: -5 + 5 = 0 0 + -6p = 49 + 5 -6p = 49 + 5 Combine like terms: 49 + 5 = 54 -6p = 54 Divide each side by '-6'. p = -9 Simplifying p = -9
| 7d=49 | | 6a=6 | | d-9=7+2d | | 5x+13=7x+5 | | 16k-10=6k | | -16d-9=7+2d | | 6a=1 | | (5g+9)7= | | -8+14= | | -2(2p-3)=3r | | 6y^2+y-15=0 | | 4s+9t-9= | | 5n-12=-3n+4 | | 4x^4+x^2-18=0 | | 9n+8=89 | | -3+8=2 | | 5a=5 | | 6x^2-9=0 | | 4(2+5)=x | | 5n-12=3n+4 | | 17-x=7 | | 5a=1 | | 5(n+2)=-17q | | -3x-9=-18 | | 2.4=.2t | | 12x+6=11-4x | | 14+3(x+8)=20 | | 4.9=.7k | | z^5-4z^3+5z=0 | | x+107=109 | | 3-2y=-7 | | 13-4r=1-x |